Mapping characteristics and financial importance of development banks across the world - Porenta, Jan (Economic and business review, 2024)
This paper investigates the financial importance of development banks across regions and income groups. We construct a global banking dataset for the period 1995 to 2021 and analyse the distribution of development banking assets across macro regions and country income groups. We create a composite global and national Development Bank Financial Importance index (DBFI index) that enables us to rank the most financially important development banks across the globe. Development banks play significant and diverse roles in the global financial system, but their financial importance varies across regions and income groups. The paper offers a broad analysis of the global development banking landscape and advances the area of research further.
Keywords: analize; analysis; bančništvo; banking; finance; regional economic development; regionalni razvoj